Leprose do citros : interações planta x vírus x vetor - Nicolini-Teixeira, Fernanda (2008)
The leprosis, caused by the virus of the citrus leprosis (Citrus leprosis virus - CiLV) is one of the main viruses of the Brazilian citrus industry. In order to quantify the virus through the technique of RT-qPCR and understand the patossistema plant - virus - vector, both in plants of citrus, as in the mite vector, led to two experiments at the Centre APTA Citrus Sylvio Moreira/IAC. In the experiment of quantification of virus in the host plant has used up three genotypes of citrus, pear and orange (C. sinensis (L.) Osbeck), tangor Murcott (C. sinensis x C. reticulata Blanco) and Golden file. Mites of people kept in the Laboratory Acarologia 72 hours a source of inoculum (sheets of orange pear with symptoms of leprosis) for the purchase of the virus. The mites were viruliferous transferred for leaves of the three genotypes under study, with five repetitions each. These leaves were collected inthe proposed time at work and immediately after each collectio, submerged in liquid nitrogen and stored in a freezer -80°C for the extraction of RNA and subsequent summary of the cDNA. The absolute quantification was performed by RT-qPCR with TaqMan system. As a positive control were used sheets of orange pear with symptoms, added to the reactions of the standard curve of the gene studied, in all slabs of qPCR.